Mesoscale-convective processes in the atmosphere - Trapp, Robert J. (Robert Jeffrey), 1963-; Cambridge eBooks (Cambridge : Cambridge University Press, 2013)
This new textbook seeks to promote a deep yet accessible understanding of mesoscale-convective processes in the atmosphere. Mesoscale-convective processes are commonly manifested in the form of thunderstorms, which are fast evolving, inherently hazardous, and can assume a broad range of sizes and severity. Modern explanations of the convective-storm dynamics, and of the related development of tornadoes, damaging 'straight-line' winds and heavy rainfall, are provided. Students and weather professionals will benefit especially from unique chapters devoted to observations and measurements of mesoscale phenomena, mesoscale prediction and predictability, and dynamical feedbacks between mesoscale-convective processes and larger-scale motions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Atmospheric thermodynamics; Electronic books